2000
DOI: 10.1074/jbc.275.8.5512
|View full text |Cite
|
Sign up to set email alerts
|

The Human AC133 Hematopoietic Stem Cell Antigen Is also Expressed in Epithelial Cells and Targeted to Plasma Membrane Protrusions

Abstract: The human AC133 antigen and mouse prominin are structurally related plasma membrane proteins. However, their tissue distribution is distinct, with the AC133 antigen being found on hematopoietic stem and progenitor cells and prominin on various epithelial cells. To determine whether the human AC133 antigen and mouse prominin are orthologues or distinct members of a protein family, we examined the human epithelial cell line Caco-2 for the possible expression of the AC133 antigen. By both immunofluorescence and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

26
351
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(378 citation statements)
references
References 25 publications
26
351
0
1
Order By: Relevance
“…As a positive control, we examined a 54-day gestation gut tissue and detected CD133 at apical edges of cells in the lumens as described earlier (Corbeil et al, 2000) ( Figure 2a). We observed clear staining above background in 10 of 32 primary serous epithelial ovarian cancers that was present at variable intensity and primarily at the luminal edges of glandular structures ( Figure 2a and Supplementary Figure S3).…”
Section: Cd133 Is Expressed By Many Ovarian Cancer Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a positive control, we examined a 54-day gestation gut tissue and detected CD133 at apical edges of cells in the lumens as described earlier (Corbeil et al, 2000) ( Figure 2a). We observed clear staining above background in 10 of 32 primary serous epithelial ovarian cancers that was present at variable intensity and primarily at the luminal edges of glandular structures ( Figure 2a and Supplementary Figure S3).…”
Section: Cd133 Is Expressed By Many Ovarian Cancer Cell Linesmentioning
confidence: 99%
“…Cancer stem cells have been identified in a growing number of hematopoietic and solid tissue malignancies and are typically recognized by virtue of the expression of cell surface markers. The pentaspan transmembrane glycoprotein CD133, also known as Prominin-1, was originally described as a hematopoietic stem cell marker (Yin et al, 1997) and was subsequently shown to be expressed by a number of progenitor cells including those of the epithelium, where it is expressed on the apical surface (Corbeil et al, 2000). CD133 expression distinguishes a number of cancer-initiating cells, including those associated with brain (Singh et al, 2004;Liu et al, 2006), pancreatic (Olempska et al, 2007), liver (Ma et al, 2002;Yin et al, 2007), skin (Monzani et al, 2007), prostate (Collins et al, 2005;Miki et al, 2007) and colon cancers (O'Brien et al, 2007;Ricci-Vitiani et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…CD133 expression has been detected in several normal tissues including neuroepithelium, embryonic and adult immature epithelia (Weigmann et al, 1997;Corbeil et al, 2000;Richardson et al, 2004;Shmelkov et al, 2005). The association between CD133 and CSCs has been documented in haematological malignancies (Horn et al, 1999) and since then, CD133 expression has been identified in various types of solid tumours, including brain tumours (Singh et al, 2003(Singh et al, , 2004Beier et al, 2007), prostate cancer (Collins et al, 2005), kidney cancer (Florek et al, 2005), melanoma (Klein et al, 2007;Monzani et al, 2007), ovarian cancer (Ferrandina et al, 2007), hepatocellular carcinoma (Suetsugu et al, 2006;Ma et al, 2007;Yin et al, 2007), and colon cancer (Ieta et al, 2007;O'Brien et al, 2007;Ricci-Vitiani et al, 2007).…”
mentioning
confidence: 99%
“…8 CD133, a transmembrane glycoprotein, is also a marker of haematopoietic SC. 9,10 In the epidermis, SC are believed to be among the beta 1 integrin-positive population of cells. 11 Nestin, an intermediate filament, has been proposed as a marker of neural SC (and TAC).…”
mentioning
confidence: 99%